Association between angiotensin converting enzyme gene insertion/deletion polymorphism and intracerebral haemorrhage in North Indian population: a case control study and meta-analysis - Kumar, A.; Prasad, K.; Vivekanandhan, S.; Srivastava, A.; Goswami, S.; Srivastava, M. V. P.; Tripathi, M. (Neurological sciences, 2014)
The purpose of this study was to determine the relationship between Angiotensin converting enzyme (ACE) insertion/deletion polymorphism and ICH with an ACE level in a North Indian population. Patient with ICH and age- and sex- matched control subjects were recruited. Case control study design was used. Genotyping was performed by using Polymerase chain reaction. Serum ACE levels were measured by colorimetric method. Our results were integrated with other reported studies across different countries in a meta-analysis. One hundred and six patients with ICH and 106 age- and sex- matched control subjects were recruited. Mean age of cases and control subjects were 53.4 ± 1 and 52.9 ± 13.4, respectively. The DD genotypes were more frequency distributed in cases compared with controls (OR 2; 95 % CI, 1.02–3.8, P = 0.04) under a recessive model of inheritance. Meta-analysis suggests significant association between ACE I/D polymorphism and risk of ICH (OR 1.98; 95 % CI, 1.53–2.57) under the recessive model of inheritance and under the dominant model of inheritance (OR 1.31; 95 % CI, 1.18–1.45). The findings of the present study show a significant association between ACE insertion/deletion polymorphism and ICH. Meta-analysis indicate that ACE I/D polymorphism may be a susceptible marker for risk factor of ICH in Asian population.